فاعلية برنامج تدريبي قائم على نموذج بار - أُن في تنمية مهارات الذكاء الانفعالي لدى طالبات الصف الحادي عشر بمحافظة مسقط سلطنة عمان - حارثي، عائشة بنت حمد بن محمد (Kulliyah of Education, International Islamic University Malaysia, 2017)
Adolescence is a sensitive transitional stage where adolescents experience a variety of emotional, cognitive and physical changes. Hence, adolescents need training and rehabilitation programs to prevent them from various problems. This study aims to reveal the effectiveness of a training program based on the Bar-On model in improving sound emotional intelligence skills amongst 11th grade female students in the governorate of Muscat in the Sultanate of Oman. The study consisted of sixty-two (62) female students, aged sixteen to seventeen years old, selected from the Shati Qurum Public School, Directorate General of Education in Muscat Governorate, in the first semester of the academic year 2016/17. The sample was divided into two groups, the experimental group, consisting of thirty-one students, and the control group, consisting of thirty-one students. In order to achieve the objective of the study, the researcher prepared a training program based on Bar-On's model for developing emotional intelligence skills. This program consisted of seventeen guided training sessions, given twice a week for forty-five minutes, and distributed over the six dimensions of the emotional intelligence scale. The researcher also used the Bar-On model (EQ-1:YV) on emotional intelligence of children and teenagers. This model is designed to measure the emotional intelligence of students whose ages range from seven to eighteen years old. The researcher verified the scale validity through experts. Furthermore, the overall scale reliability was examined by Cronbach's Alpha test of internal consistency, which was (0.866), and the test-retest reliability (0.563). The results of the study indicated that there were statistically significant differences in the mean scores of the students' performance in all aspects of the emotional intelligence in favor of the experimental group. However, there was no statistically significant difference in the mean scores for stress management scale. The study recommends the importance of adopting emotional intelligence skills in the planning and developing projects of educational curricula, and utilize these skills in the educational content for all the educational stages.